Vanderwood Meadow Farms : sustainable growth - Shanahan, Doreen E.; Rapier, Stephen M. (London : SAGE Publications Ltd, 2017)
Started in 2011, Vanderwood Meadow Farms supplied local retailers in Minneapolis, Minnesota with fresh, locally grown leafy greens and herbs cultivated using revolutionary vertical farming techniques. The company's leadership team was committed to advancing sustainable crop production. More specifically, a method for sustainable crop production called aquaponics which they felt was best suited for urban cities and highly populated geographic areas where the local climate didnt permit year-round farming. The mission of the company was focused on creating "local food systems" providing solutions for retailers to acquire sustainably produced and locally sourced produce for their customers. Core to their brand message was their commitment to sustainable farming, which encompassed environmental responsibility as well as socioeconomic responsibility. By the fall of 2015 the company encountered a state of growth where demand for its products exceeded supply and growth was limited by the company's capacity to deliver its products. While the company continued to make investments to maximize capacity at its current location, management was eager to expand geographically to serve new markets furthering their mission. Contemplating expansion, Vanderwood Meadow Farms new CEO asked, "How do we know that a product that sells well in one market will sell just as well in others? I want to understand why consumers are attracted to our locally sourced goods, so that we can leverage that understanding to successfully expand to new markets."
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Vanderwood Meadow Farms; Marketing; Sustainable development; Food industry and trade